2018
DOI: 10.18483/ijsci.1479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formalin Toxicity among Preclinical I Medical Students, Adigrat University, Ethiopia

Abstract: Introduction:Formalin is a colorless gas with a pungent odor. Because of its germicidal efficacy it is widely used as a preservative for human cadaver in the anatomy laboratory. Acute exposure to formaldehyde results in irritation and burning of the mucous membranes of the nose, mouth, upper respiratory tract, depression, headache, nausea, coughing, irritation and burns to the skin and eye. Objective: The purpose of this study is to assess the effects of formalin toxicity among preclinical-I medical students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…This finding was consistent with a study carried out in Ethiopia by Hagos et al, who revealed that the most common toxic effect of formalin on the medical students was the unpleasant smell (84.4%). 14 Another study conducted in India by Abhijeet and Mukul; also revealed that the most commonly reported symptoms related to the effects of formalin were the unpleasant smell (30%) followed by Unusual tiredness or dizziness (25.3%). 3 Moreover, Kundu and Gangrade conducted a study on Indian medical students and found that the most common reported symptom among medical students was unpleasant smell (94.68%).…”
Section: Discussionmentioning
confidence: 96%
“…This finding was consistent with a study carried out in Ethiopia by Hagos et al, who revealed that the most common toxic effect of formalin on the medical students was the unpleasant smell (84.4%). 14 Another study conducted in India by Abhijeet and Mukul; also revealed that the most commonly reported symptoms related to the effects of formalin were the unpleasant smell (30%) followed by Unusual tiredness or dizziness (25.3%). 3 Moreover, Kundu and Gangrade conducted a study on Indian medical students and found that the most common reported symptom among medical students was unpleasant smell (94.68%).…”
Section: Discussionmentioning
confidence: 96%